Likopen Tomat sebagai Agen Epigenetik dalam Regulasi Gen Proinflamasi melalui Jalur NF-ΚB - Rayhana Azzahra Kusmana (Pusat riset dan Inovasi Nasional, 2025)
Chronic inflammation is a complex condition that involves the activation of the transcription factor NF-κB, which plays an important role in inducing the expression of proinflammatory genes such as TNF-α, IL-1β, and IL-6. Activation of this pathway is often associated with degenerative diseases, including cancer, cardiovascular disease, as well as metabolic disorders. Lycopene, the main carotenoid pigment in tomatoes, is known as a potent antioxidant with anti-inflammatory properties, but its epigenetic mechanism in the regulation of inflammatory gene expression is still a growing area of research. This article aims to review the recent literature on the role of lycopene as an epigenetic agent capable of modulating the expression of proinflammatory genes through epigenetic pathways associated with NF-KB. This research method uses a systematic literature review through PubMed, Google Scholar, and Scopus databases with a publication range of 2015–2025. The results of the study show that lycopene works through several important mechanisms. First, lycopene can affect DNA methylation in the promoter region of inflammatory genes by inhibiting the enzyme DNA methyltransferases (DNMT), which has an impact on decreased transcription of proinflammatory genes. Second, lycopene plays a role in histone modification, especially by inhibiting histone deacetylases (HDAC) thereby increasing histone acetylation of H3K9 in anti-inflammatory genes. Third, lycopene is able to regulate microRNA expression such as lowering miR-155 and miR-21 which strengthen the NF-κB pathway, while increasing miR-146a which plays a role in suppressing inflammation. Fourth, lycopene directly inhibits NF-κB activation by targeting IκB kinase (IKK), preventing IκB degradation, and lowering the translocation of the p65 subunit to the nucleus. With such a dual mechanism, tomato lycopene has the potential to be an effective nutraceutical agent for chronic inflammatory therapy.